Pengaruh Kesetaraan Gender, Transaksi Pihak Berelasi, dan Modal Intelektual Hijau Terhadap Manajemen Laba - Mochammad Razel Putra Zalna; Christina Dwi Astuti (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to examine the effect of gender equality, related party transactions, and green intellectual capital on earnings management. The sample used in this study is manufacturing companies listed on the Indonesia Stock Exchange (IDX) for 2021-2023, totaling 166 observations obtained using purposive sampling technique. This study uses multiple regression analysis methods using SPSS 29.0. The results of this study indicate that partially only gender equality has a negative effect on earnings management. Meanwhile, related party transactions and green intellectual capital have a positive effect on earnings management. The results of this study simultaneously show that gender equality, related party transactions and green intellectual capital have an influence on earnings management.